2018
DOI: 10.1007/s10897-018-0216-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Counseling in the Era of Genomics: What's all the Fuss about?

Abstract: As genomic sequencing becomes more widely available in clinical settings for diagnostic purposes, a number of genetic counseling issues are gaining precedence. The ability to manage these issues will be paramount as genetic and non-genetic healthcare professionals navigate the complexities of using genomic technologies to facilitate diagnosis and inform patient management. Counseling issues arising when counseling for diagnostic genomic sequencing were identified by four genetic counselors with 10 years of col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Eighty‐three percent of the 121 parents in our quantitative study experienced no regret or mild regret regarding their decision to pursue GWS, as measured by the Decisional Regret Scale, administered a month after receiving results. This is consistent with three previous studies that utilized the DRS at varying times post results and with varying sample sizes (Aldridge et al., 2021; Brett et al., 2018; Wynn et al., 2018). One of these studies also found an interesting, but not statistically significant, association between decisional regret and type of result: Wynn et al studied 192 participants and collected DRS data a mean of 16 months (range 1–42 months) post results.…”
Section: Discussionsupporting
confidence: 91%
“…Eighty‐three percent of the 121 parents in our quantitative study experienced no regret or mild regret regarding their decision to pursue GWS, as measured by the Decisional Regret Scale, administered a month after receiving results. This is consistent with three previous studies that utilized the DRS at varying times post results and with varying sample sizes (Aldridge et al., 2021; Brett et al., 2018; Wynn et al., 2018). One of these studies also found an interesting, but not statistically significant, association between decisional regret and type of result: Wynn et al studied 192 participants and collected DRS data a mean of 16 months (range 1–42 months) post results.…”
Section: Discussionsupporting
confidence: 91%
“…As genomic sequencing has become available in pediatric clinical genetics settings, genetic counselors have been called upon to support individuals and families through the testing process (Brett et al, ; Facio, Lee, & O'Daniel, ; Hooker, Ormond, Sweet, & Biesecker, ; Ormond et al, ; Patch & Middleton, ). The importance of pretest counseling for facilitating informed consent to genetic and genomic testing has been established (ACMG Board of Directors, ; Arora, Haverfield, Richard, Haga, & Mills, ; Bowdin, Hayeems, Monfared, Cohn, & Meyn, ; Uhlmann, Schuette, & Yashar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some have argued that genomic medicine will result in significant changes to genetic counseling practice (Ormond, 2013), whereas others suggest that GCs already possess the skills required to practice when this new technology is applied (Brett et al., 2018). Either way, GCs are likely to play a vital role in managing the expectations of both health professionals and patients with regard to genomic sequencing (Brett et al., 2018; Hooker et al., 2014). With any new technology, hopes can exceed reality; this is particularly true for genomic technologies in pediatric acute care (Fenn & Raskino, 2008).…”
Section: Introductionmentioning
confidence: 99%